Case-control study in ALS using the National ALS Registry: lead and agricultural chemicals are potential risk factors. Issue 3 (3rd April 2022) - Mitsumoto, Hiroshi; Garofalo, Diana C.; Gilmore, Madison; Andrews, Leslie; Santella, Regina M.; Andrews, Howard; McElhiney, Martin; Murphy, Jennifer; Nieves, Jeri W.; Rabkin, Judith; Hupf, Jonathan; Horton, D. Kevin; et al.
Abstract: Objective : To identify occupational risk factors for ALS using well-characterized participants with ALS (P-ALS), sibling controls (S-controls), and matched population controls (P-controls) within the National ALS Registry. We also compared oxidative stress (OS) biomarkers between groups. Methods : P-ALS were recruited over 4 years. Demographic, socioeconomic, and medical data were ascertained from medical records and structured interviews. P-ALS were followed prospectively for 2 years or until death, whichever came sooner. S-controls and age-, sex-, race/ethnicity-, and residential location-matched P-controls were recruited over 3 years. Occupational exposure to lead and agricultural chemicals (ACs) were assigned by an occupational hygienist, blinded to case status. OS biomarkers in urine were measured. Results: P-ALS (mean age 62.8 years; 63% males) resided across the United States. Demographic and socioeconomic variables did not differ among P-ALS, S-controls, and P-controls. P-ALS were more likely to report occupations with exposure to lead (adjusted OR (aOR)=2.3, 95% CI 1.1, 4.6) and ACs (aOR = 2.4, 95% CI 1.2, 4.6) compared to pooled controls. Among those with occupations with exposure to both lead and ACs, aOR was 7.2 (95% CI 2.0, 26.1). Urinary 8-oxo-dG was significantly elevated among P-ALS (11.07 ± 5.42 ng/mL) compared to S-controls, P-controls, or pooled controls (pooled 7.43 ± 5.42 ng/mL; p  < 0.0001) but was not associated with occupational exposure to either lead or ACs. Conclusions : Findings reveal increased risk of ALS diagnosis among those with occupational exposure to lead and ACs and increased OS biomarkers among cases compared to controls. OS may be an important pathogenic mechanism in ALS.